A novel approach to glycemic control in type 2 diabetes mellitus, partial jejunal diversion: pre-clinical to clinical pathway. Issue 1 (1st September 2017) - Fried, Martin; Dolezalova, Karin; Chambers, Adam P; Fegelman, Elliott J; Scamuffa, Robin; Schwiers, Michael L; Waggoner, Jason R; Haluzik, Martin; Seeley, Randy J
Abstract : Objective: To explore partial jejunal diversion (PJD) via a side-to-side jejuno-jejunostomy for improved glycemic control in type 2 diabetes mellitus (T2DM). PJD is an anatomy-sparing, technically simple surgery in comparison to the predominate metabolic procedures, Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG). Positive results in a rodent model prompted a human proof-of-concept study. Research design and methods: Pre-clinically, 71 rats were studied in a model of metabolic dysfunction induced by a high-fat diet; 33 animals undergoing one of two lengths of PJD were compared with 18 undergoing sham, 10 RYGB and 10 jejuno-ileal bypass. Clinically, 15 adult subjects with treated but inadequately controlled T2DM (hemoglobin A1c (HbA1c) of 8.0%–11.0%), body mass index of 27.0–40.0 kg/m 2, and C peptide ≥3 ng/mL were studied. Follow-up was at 2 weeks, and 3, 6, 9, and 12 months post-PJD. Results: Pre-clinically, positive impacts with PJD on glucose homeostasis, cholesterol, and body composition versus sham control were demonstrated. Clinically, PJD was performed successfully without serious complications. Twelve months post-surgery, the mean (SD) reduction from baseline in HbA1c was 2.3% (1.3) (p<0.01). Conclusions: PJD may provide an anatomy sparing, low-risk, intervention for poorly controlled T2DM without significant alteration of the patient's lifestyle. The proof-of-concept study is limited by a small sample size and advanced disease, with 80% of participants on insulin and a mean time since diagnosis of over 10 years. Further study is warranted. Trial registration number: NCT02283632; Pre-results.